Pola sebaran tingkat infeksi bersama serotipe virus dengue di wilayah kajian RT-PCR Balai Besar Teknik Kesehatan Lingkungan dan Pengendalian Penyakit Yogyakarta: analisis data 2013-2015 - Fitria Wakano; Lutfan Lazuardi; Eggi Arguni; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Pattern of concurrent infection of dengue virus serotype in the regional study areas of Yogyakarta Center for Environmental Health and Diseases Control: an analysis of 2013-2015 dataPurposeThis study aimed to determine the pattern in the spread of infection rates with dengue viral serotypes.MethodsThe study was a descriptive research with spatial mapping methods. Data of 132 respondents were collected based on RT-PCR in 2013-2015. The complete address of the village-level patient from the dengue arbovirosis surveillance data of the Center for Environmental Health and Diseases Control Yogyakarta were used to determine the coordinate points with utilization of RBI and Google Earth maps in searching addresses for distribution of case coordinate points. ResultsThere were similarities with the most complex quadruple joint infection rates of DEN in Semarang and Yogjakarta, while Kebumen obtained double DEN level. Three patterns of infection with DEN-1 and DEN-3 have p-value < 0.05 in Semarang in 2014, Sragen in 2015 and Semarang 2013 and 2 patterns in Gunung Kidul 2014 and Kulon Progo 2015. The patterns of infection with DEN-1, DEN-2 and DEN-3 in 2015 were covering Sragen and Semarang in 2013.ConclusionThe most complex areas of infection were Semarang and Yogyakarta. The pattern of most likely cluster infection with DEN-1 and DEN-3 and DEN-1, DEN-2 and DEN-3 allegedly was a result of two infected patients, different serotypes of different mosquitoes or infection of more than one serotype of Ae. aegypti or Ae. albopictus as the main vector.